An exploratory study of the relevance of therapy format and therapist’ training in individual cognitive behavioral therapy for psychosis - Gjerdalen, Oda Skancke; Zucknick, Manuela; Westlie, Ingvild Tvedt; Bull, Helen; Evensen, Stig; Falkum, Erik; Grande, Marit; Hagen, Roger; Romm, Kristin Lie; Jensen, Lene Hunnicke; Ringen, Petter Andreas; Schjøtt-Pedersen, Olivia; et al. (Frontiers in Psychiatry, 2025)
IntroductionCognitive Behavioral Therapy for psychosis (CBTp) is an evidence-based intervention that can be delivered in various formats, including as part of vocational rehabilitation. However, due to scarcity of resources, CBTp is currently accessible to only a minority of individuals with psychosis. This secondary analysis aims to explore potential differences in clinical outcomes between distinct CBTp formats and to examine whether therapist training influences treatment effect. Exploring these aspects is of importance, as they may influence the scalability and accessibility of CBTp in routine care.Material and methodsData in this study is sourced from two independent projects; KATOslo and JUMP, comprising a total of 200 participants with broad schizophrenia-spectrum disorders. The current study compares CBTp delivered as either symptom-focused individual therapy (KATOslo) or as an add-on to a vocational rehabilitation (VR) program (JUMP), with two reference groups; VR combined with cognitive remediation (JUMP) and treatment as usual (KATOslo). Using a series of mixed effects models for repeated measurements, we examined differences between the groups in terms of general functioning and psychiatric symptom severity. Emphasis was placed on potential differences between the two groups receiving CBTp, considering both average differences across assessment points and trajectories over time.ResultsIn line with expectations, all groups demonstrated overall improvements in functioning and symptom levels. After adjusting for relevant confounders, no statistically significant differences were found between the two groups receiving CBTp following treatment initiation.ConclusionsThese findings suggest that CBTp may be effective across different delivery formats and levels of therapist training in terms of similar, positive clinical outcomes for this patient group. This has potential implications for service design and broader implementation of CBTp in real-world settings.